2020
DOI: 10.1177/2633366x20926520
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hygrothermal aging on the mechanical properties of IMA/M21E aircraft-grade CFRP composite

Abstract: Unidirectional carbon fiber-reinforced plastic (CFRP) IMA/M21E polymer composite was manufactured by standard autoclave curing method. This is a new aircraft-grade CFRP composite presently used in the manufacture of aircraft wing parts. Test specimens as per ASTM standards for weight gain, tensile and compression tests were obtained from this composite laminates. Some of the test specimens were subjected to hygrothermal (hot–wet) aging in an environmental chamber under three different conditions, that is, (i) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…It can be observed that a slight decrease in tensile strength, approximately 3.52% with respect to that of dry specimens, due to water absorption can be observed in Figure 6a. According to Shetty et al [33], the degradation of mechanical properties of their GFRP samples is linearly proportional with the degree of moisture content. This is caused by the decrease of fibre-matrix interfacial strength as has been reported by Eslami et al for GFRP composites [34].…”
Section: Tensile Strengthmentioning
confidence: 99%
“…It can be observed that a slight decrease in tensile strength, approximately 3.52% with respect to that of dry specimens, due to water absorption can be observed in Figure 6a. According to Shetty et al [33], the degradation of mechanical properties of their GFRP samples is linearly proportional with the degree of moisture content. This is caused by the decrease of fibre-matrix interfacial strength as has been reported by Eslami et al for GFRP composites [34].…”
Section: Tensile Strengthmentioning
confidence: 99%
“…Priority is given to high-tech industries Criteria Decision Making (MCTM) problem and at the highest level of the decision-making process has For this purpose, SWARA and COPRAS Methods as approaches to solve this problem were used. SWARA is a new in MCDM A powerful method, it is one of policy making [25]. The COPRAS method is the most available outperforms classical MADM methods, Because it assesses the utility level of alternatives, This is in addition to an assessment of the market value of the alternatives Is it better than other alternatives taken for comparison Or worse shows.…”
Section: Coprasmentioning
confidence: 99%
“…During their service life, aircraft and automobiles are constantly exposed to a wide range of environmental conditions, such as sudden changes in temperature, precipitation, solar radiation, salt fog, and environmental pollution, in addition to the combination of these factors with mechanical loads. These factors can influence and/or accelerate the degradation of mechanical and physical properties, so it is essential to know the operating environment in which the component will be exposed during its service life, minimizing the need for advanced maintenance and even its replacement [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%